واقع تطبيق منهج Lean Six Sigma في المؤسسات الاقتصادية الجزائرية الحاصلة على شهادة الايزو- دراسة حالة مؤسسة" نفطال" بالجزائر العاصمة - بن سعيد, حياة; زياني, عبد الحق (جامعة الوادي - University of Eloued, 2023)
This study aimed to analyze the reality of the application of the Lean Six Sigma approach in the Algerian economic enterprises that obtained the ISO certificate through a case study of the "Naftal" institution in Algiers, and in order to achieve the purposes of the study and complete the theoretical side, the researchers designed a questionnaire that included (14) phrases to collect the necessary information from the study sample consisting of (38) individuals, data analysis and hypothesis testing using the SPSS program. The study concluded that there is awareness by members of the target sample of the benefits of the Lean Six Sigma approach, in addition to the presence of obstacles that hinder the application of this approach in the economic enterprise "Naftal", due to several justifications, most notably the lack of management knowledge of the stages of its applying
The reality of the application of the Lean Six Sigma approach in the Algerian economicenterprises that obtained the ISO certificate- Case study of the "Naftal" institution in Algiers
مقال
Keywords: lean system, six sigma approach, lean six sigma approach, DMAIC methodology